Using an extended theory of planned behaviour to measure intention to contribute to cash waqf - Nur Shafawati binti Bahara (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
Cash waqf has signalled a significant change in the waqf system and has been generally accepted as a valid waqf practice considering its importance in developing waqf institutions and enhancing the socio-economy of the community. Yet, the literature that discusses the social psychological factors underlying an individual's decision to donate cash waqf remains limited. Therefore, this study seeks to identify the factors that influence the donor's (waqif) intention to participate in cash waqf in the perspective of Malaysian Muslims, particularly in the Klang Valley area based on the original Theory of Planned Behaviour (TPB). The study proposes seven factors comprising attitude, perceived behaviour control, injunctive norms, descriptive norms, moral norms, past behaviour and awareness. Two hundred and eighty-eight questionnaires were collected and data were analysed using multiple regression analysis. A 5-point Likert-scale was constructed to measure the donor's (waqif) giving intention behaviour. The findings reveal that attitude, injunctive norms, perceived behavioural control, moral norms and past behaviour have significant effect on determining cash waqf participation. While intention positively influences the cash waqf giving behaviour, this study supports the applicability of the theory of planned behaviour and the extended variables in a new context of cash waqf. The findings have broadened the understanding of charitable donation intention and its antecedents in the context of cash waqf.